IMPACT OF VITAMIN E AND SELENIUM ADMINISTRATION DURING PERIPARTURIENT PERIOD ON REPRODUCTIVE PERFORMANCE OF SURTI BUFFALO - MODI, L C; KHASATIYA, C T; PATEL, M D; MODI, FALGUNI (The Indian Journal of Animal Reproduction, 2022)
The study was conducted on Surti buffalo (n=20) during the periparturient period. Treatment group buffalo (n=10) were administered vitamin E and Selinium (Inj. E-CARE Se 10 ml, i.m.) on days 60, 45, 30 and 15before the expected date of parturition and after parturition on days 15 and 30. In treated buffalo, the time for involution of uterus as well as service period was shorter as compared to controls (p<0.05). Conception rate was higher in buffalo receiving antioxidant therapy. In brief, the administration of anti-oxidants at regular interval during the periparturient period may help to improve the reproductive performance of buffalo.